2016
DOI: 10.1371/journal.pmed.1002115
|View full text |Cite
|
Sign up to set email alerts
|

An Audit and Feedback Intervention for Reducing Antibiotic Prescribing in General Dental Practice: The RAPiD Cluster Randomised Controlled Trial

Abstract: BackgroundDentists prescribe approximately 10% of antibiotics dispensed in UK community pharmacies. Despite clear clinical guidance, dentists often prescribe antibiotics inappropriately. This cluster-randomised controlled trial used routinely collected National Health Service (NHS) dental prescribing and treatment claim data to compare the impact of individualised audit and feedback (A&F) interventions on dentists’ antibiotic prescribing rates.Methods and FindingsAll 795 antibiotic prescribing NHS general dent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
144
3
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(151 citation statements)
references
References 32 publications
0
144
3
1
Order By: Relevance
“…1). We identified 12 CFIR + TDF articles; the final list of included studies comprised five protocols for empirical studies (Gould [22], Prior [23], Manca [24], Graham-Rowe [25], Sales [26]) and seven completed empirical studies (Murphy [27], English [28], Bunger [29], Moullin [30], Newlands [31], Templeton [32], Elouafkaoui [33]).
Fig. 1PRISMA flow diagram
…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1). We identified 12 CFIR + TDF articles; the final list of included studies comprised five protocols for empirical studies (Gould [22], Prior [23], Manca [24], Graham-Rowe [25], Sales [26]) and seven completed empirical studies (Murphy [27], English [28], Bunger [29], Moullin [30], Newlands [31], Templeton [32], Elouafkaoui [33]).
Fig. 1PRISMA flow diagram
…”
Section: Resultsmentioning
confidence: 99%
“…Two completed studies and two protocols described intervention design and/or implementation plans (Gould [22], Sales [26], Murphy [27], English [28]); one protocol described a comparison of the effectiveness of an intervention relative to standard care (Prior [23]), and two protocols and five completed studies evaluated interventions (Manca [24], Sales [26], Bunger [29], Moullin [30], Newlands [31], Templeton [32], Elouafkaoui [33]). Several of the included studies had multiple objectives (e.g., effectiveness study and concurrent qualitative process evaluation [23, 33]).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several other studies have also demonstrated improvements in antibiotic prescribing practices after antimicrobial stewardship interventions. 13, 20, 33, 34 These audit and feedback interventions appear to be well-received by participants. In a follow-up survey after an antibiotic audit and feedback intervention, a majority of general dentists found the experience to be both understandable and worthwhile.…”
Section: Discussionmentioning
confidence: 97%
“…In the UK, dentists prescribe ~10% of antibiotics dispensed in community pharmacies but, similarly to clinicians, they often do so against clear clinical guidelines. [11] Based on prescription data in Canada, dental prescribing increased by 62.2% (1996 -2013), with proportionate contribution to community consumption increasing from 6.7% to 11.3% of antibiotic prescriptions over the same period. [12] Although data in terms of an SA perspective are not available yet, given the unique local healthcare challenges, there is no reason to believe that it will be much different.…”
Section: Guest Editorialmentioning
confidence: 99%